Conceptual issues in psychiatric neuroimaging: an update. - Stoyanov, D; Stanghellini, G; Broome, M (2012)
AIM: In this paper, we provide an update on the conceptual issues of psychiatric neuroimaging, especially in the light of the current reductive claims of the eliminative physicalism. ARGUMENT: our argument is developed on three stages. The first is to highlight the crucial importance of phenomenological psychopathology and person-centered approach, which remains underestimated; the second is to bring forward the view that functional neuroimaging is relevant to the area of 'translation' in the mind-brain debate. The third point is to present a critical analysis of the shortcomings in structural and functional neuroimaging from methodological and epistemological perspectives. CONCLUSION: a novel paradigm for translational cross-validation among neuroscience, psychopathology and clinical psychology is presented.